The Impact of Machine Translation on English Vocabulary Acquisition: Target Language Accuracy - Iskandar Dzulkurnain, Mohammad; Sunardi,; Siswandari,; Asrowi, (International Journal of Psychosocial Rehabilitation, 2020)
It becomes experienced by most people to encounter and find out the meaning of foreign language in a text. The availability of Machine Translation (MT) since 2000s appearing in some platforms give the users’ options in such easy way through clicked and linked. For the Speakers of Other Languages (ESOL), MT contributes to their understanding of a text or submitting related assignments. It assists them who want to read and write in their native language. The use of MT is in line with the study of Second Language (L2) for ESOL as its role to support the vocabulary acquisition of target language. This paper discusses the effect of translation towards new words acquisition when they are given texts taken from the Internet. As the existence of language technologies which have the functions of automatic detection of lexical subject and translation, it eases the students to get the meaning of a word and its translation easily in the target language. The results of this study show that they get the advantage by using this MT as increasing the accuracy on lexical subject. On the other hand, it contributes negatively in long term phase in field of its accuracy as well. This study also presents the understanding of impact on the MT on language learning.